How have unintended pregnancies and contraceptive use among adolescent girls and young women changed in Uganda? Evidence from the 2014 and 2019 PMA national surveys - Simon P.S. Kibira; Mary Nakafeero; Mathew Amollo; Ronald Ssenyonga; Rawlance Ndejjo; Phil Anglewicz; Melody Kukundakwe; Mabel Luzze; Samuel Kagongwe; Victor Guma; Vivian Zalwango; Fredrick Edward Makumbi (PLoS ONE, 2025)
Unintended pregnancies among adolescent girls and young women (AGYW), and any pregnancy among adolescent girls are still a challenge, especially in Sub-Saharan Africa and Uganda. We assess prevalence of unintended pregnancy in Uganda, associated factors and contraceptive use following unintended pregnancy among adolescent girls and young women in 2014 and 2019 in Uganda. Data are from the 2014 and 2019 performance monitoring for action (PMA) surveys. There were 1,479 AGYW reporting ever/ or current pregnancy in the two surveys, 780 in 2014 and 699 in 2019. Data included socio-demographics and pregnancy intendedness. Descriptive analyses were conducted stratified by adolescent girls and young women and compared between surveys. The percent of unintended pregnancies was determined as the number of AGYW reporting unintended pregnancy divided by eligible participants. A weighted comparison of the prevalence of unintended pregnancies was made between the surveys, and statistical significance determined at a 5% type-1 error rate. All analyses were conducted with Stata version15 using svy surveyset methodology accounting for complex survey design. Relative to 2014, the 2019 survey showed a significant reduction in percent of AGYW reporting ever pregnant or given birth, 60% to 49%, p = 0.007; a decline in unintended pregnancy among adolescent girls, 52% to 42%, p = 0.049, and among young women with secondary education, 36% to 13%, p = 0.001. Conversely, the 2019 survey showed significant increase in contraception among those ever pregnant, 26% to 40%, p < 0.001; higher in young women (30% to 47%, p = 0.001) compared to adolescent girls (16% to 25%, p = 0.005). The commonest contraceptive methods were short-acting at both surveys, while the long-acting methods significantly increased among young women (20% to 35%, p = 0.003). The decline in unintended pregnancies was consistent with increased use of contraceptive methods. Although we observed a significant decline in unintended pregnancy among adolescent girls, the proportion reporting unintended pregnancy remains high.